2021
DOI: 10.1504/ijicbm.2021.10042177
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Void: How Institutional Entrepreneurship Can Overcome Institutional Voids in Indian Public Organisations

Abstract: There is limited research on the role of institutional entrepreneurship in public organisations, especially in the context of institutional voids. The public sector entrepreneurs' engagement with regulatory, normative, and cultural-cognitive institutional voids in a developing economy is, therefore, examined using institutional work. Through an in-depth longitudinal case study of Delhi Metro Rail Corporation in India, institutional creation and disruption processes are identified as interrelated means to addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…The role of transformational leadership is vital in a developing public organization. There was widespread bureaucracy, slow decision-making processes and a lack of capable leadership (Rao-Nicholson & Svystunova, 2021). This is quite similar to the findings of Seo and Creed (2002) and Greenwood and Subbady (2006), who found that the organizations they studied were confronted with the choice of "efficiency versus conformity".…”
Section: Theoretical Contributionssupporting
confidence: 80%
See 2 more Smart Citations
“…The role of transformational leadership is vital in a developing public organization. There was widespread bureaucracy, slow decision-making processes and a lack of capable leadership (Rao-Nicholson & Svystunova, 2021). This is quite similar to the findings of Seo and Creed (2002) and Greenwood and Subbady (2006), who found that the organizations they studied were confronted with the choice of "efficiency versus conformity".…”
Section: Theoretical Contributionssupporting
confidence: 80%
“…Contemporary studies on public infrastructure in India (Cui et al, 2018;Höffken & Limmer, 2019;Rao-Nicholson & Svystunova, 2021;Qiu & Rao-Nicholson, 2021;Chatterjee & Kundu, 2022) have noted the lack of relevant organizational reforms (Khanna et al, 2021) and talent to support India's growing demand for public facilities and infrastructure (Shah & Prakash, 2018;Chertow et al, 2019;Kumar, 2021). There is thus a gap in our knowledge of how organizations can leverage entrepreneurship during the process of organizational renewal or the creation of new subsidiaries (Lawrence et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation